Os limites de controle do Tribunal de Contas da União: uma análise da atuação da corte de contas no estabelecimento da política de governança pública do governo federal - Pessoa, Leanne Araújo Holanda de Paula (2019)
The purpose of the study is to analyze the control limits of the Federal Court of Accounts, based on the Court’s performance as a promoter of public governance policy in the federal government. In Brazil, the absorption of public governance took place through a movement led less by the public administration and more by the control bodies, especially the Federal Audit Court. Considering that the control institutions can assume a leading position, through of interferences in the change processes of the controlled entities, emerge the problem of investigating the way in which the Federal Court of Auditors influenced the construction of the governance policy, paying attention to the legitimacy, the limits of control of administrative discretion, as well as the principle of separation of powers. The study was carried out through theoretical and empirical research, using an inductive method, based on the collection of bibliographic data, official documents, normative instruments and doctrine, as well as through the quantitative and qualitative analysis of TCU decisions, which fostered or contributed to the definition of the governance policy of the entities of the federal public administration. The quantitative analysis aimed to verify how the Court’s progressive concern with the analysis of public governance for the federal public administration took place over the years. The qualitative analysis aimed to evaluate the way in which the TCU structured the parameters of the governance framework, how the Court applied these precepts in the inspection work, the interference in the administration’s performance, its consequences, and the advance in the limits of the power of control. In all, 81 judgments dealing with the theme were analyzed. In conclusion, it was found that the public governance policy was formulated based on the actions of the Federal Court of Accounts not resulting from the Court’s verification of the specificities or needs of administrative entities that may have been assessed in its audits, but rather from importation governance model propagated by international organizations. In addition, it was concluded that despite the relevant mission of the Court, it lacks legitimacy to establish how the Federal Executive Branch should execute and monitor public services and policies, and it was possible to observe an increasing interference of the Court in the area of competence. administrative discretion, in addition to imposing their understandings through recommendations and determinations, with the application of penalties that fall on public administrators. In promoting actions to improve public governance, the TCU must adopt a dialogical and collaborative stance to replace the adoption of sanctioning and coherent measures, in order to preserve the legitimacy of administrative decisions, providing greater receptivity, reach and effectiveness in its performance.